Decoding Green Consumer Behavior: A Bibliometric Review of Green Purchasing Decisions - Judijanto, Loso; Iswanto, Juni; Muhtadi, Muhamad Ammar (West Science Social and Humanities Studies, 2025)
This study presents a bibliometric review of green consumer behavior with a specific focus on green purchasing decisions, aiming to map the intellectual structure, research evolution, and thematic trends of the field. Utilizing data from the Scopus database and visualizing networks through VOSviewer, the study analyzes keyword co-occurrence, author co-citation, and country collaboration to uncover the major contributors, conceptual clusters, and temporal dynamics within the literature. The findings highlight the centrality of core themes such as “green consumer behavior,” “sustainability,” and “green marketing,” alongside emerging interests in “green purchase intention,” “environmental knowledge,” and “social media.” Influential authors including Ajzen, Stern, and Hair reflect the field’s grounding in psychological theory and marketing analytics. Country collaboration maps underscore the increasing prominence of India, China, and Indonesia in the global research landscape. While the field shows theoretical richness and interdisciplinary integration, it continues to face challenges such as the attitude–behavior gap and over-reliance on self-reported data. This review offers a comprehensive synthesis of current knowledge and suggests future research directions for enhancing sustainable consumer practices worldwide.